2018
DOI: 10.1111/1365-2745.13114
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical scenarios modulate seagrass resistance to small‐scale perturbations

Abstract: 1. Seagrasses constitute a key coastal habitat world-wide, but are exposed to multiple perturbations. Understanding elements affecting seagrass resistance to disturbances is critical for conservation. Distinct biogeographical scenarios are intrinsically linked with varying ecological and evolution backgrounds shaped across millennia.2. We addressed whether the resistance (change in shoot abundances) and performance (change in leaf morphology and growth) of the seagrass Cymodocea nodosa to a local stressor, lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 53 publications
1
36
1
Order By: Relevance
“…We found antagonistic interactions resulting from the combination of chronic nutrient increase and temperature rise for chlorophyll content and total non-structural carbohydrates in rhizomes, only in plants growing in eutrophic conditions. Intraspecific variations in terms of resistance and performance are widely documented in seagrasses (e.g., Dattolo et al, 2014;Sandoval-Gil et al, 2014;Zhang et al, 2014;Marín-Guirao et al, 2016;Procaccini et al, 2017;Beca-Carretero et al, 2019;Tuya et al, 2019) The differential responses showed in our study further confirm that P. oceanica can have different levels of plasticity in response to changes of environmental conditions. According to our results, plants from nutrient enriched conditions, which are very fragile and FIGURE 3 | Endpoints measured in OL (oligotrophic) and EU (eutrophic) plants after 5 weeks of the exposure to high temperature and nutrient enrichment.…”
Section: Discussionsupporting
confidence: 82%
“…We found antagonistic interactions resulting from the combination of chronic nutrient increase and temperature rise for chlorophyll content and total non-structural carbohydrates in rhizomes, only in plants growing in eutrophic conditions. Intraspecific variations in terms of resistance and performance are widely documented in seagrasses (e.g., Dattolo et al, 2014;Sandoval-Gil et al, 2014;Zhang et al, 2014;Marín-Guirao et al, 2016;Procaccini et al, 2017;Beca-Carretero et al, 2019;Tuya et al, 2019) The differential responses showed in our study further confirm that P. oceanica can have different levels of plasticity in response to changes of environmental conditions. According to our results, plants from nutrient enriched conditions, which are very fragile and FIGURE 3 | Endpoints measured in OL (oligotrophic) and EU (eutrophic) plants after 5 weeks of the exposure to high temperature and nutrient enrichment.…”
Section: Discussionsupporting
confidence: 82%
“…However, this study could indicate a mechanism of adaptation of this seagrass, as has been observed in other seagrasses (Shafer et al, 2007;Stephens et al, 2019), favoring its steady presence in the intertidal over almost six years in this region. In fact, these observations do not concur with other results that show low resistance to local disturbances and environmental stress in the Canary Islands' seagrass meadows, because of their low genetic diversity compared to Mediterranean populations (Tuya et al, 2019). Thus, if the establishment of C. nodosa in intertidal areas is confirmed, it would pose new questions related to the environmental management and conservation status of this endangered species.…”
Section: Resultscontrasting
confidence: 71%
“…However, it is also common to find seagrasses that prefer sediment substrates like Amphibolis Antarctica, Thalassodendron pachyrhizum or T. ciliatum growing on hard substrates (den Hartog, 1970;Kirkman & Kuo, 1990) Despite this study being mostly descriptive, its aim is to highlight the continuous presence of C. nodosa over time in an environment, such as intertidal pools, considered extreme for most seagrasses (Hemminga & Duarte, 2000). Most references related to C. nodosa in the Canary Islands have underlined the limiting role that environmental conditions play in its distribution and structure (e. g. Barberá et al, 2005;Pávon-Salas et al, 1998;Pavón-Salas et al, 2000;Tuya et al, 2019). One of the main limiting factors for the distribution of this species is water hydrodynamics (Infantes, Orfila, Bouma, Simarro, & Terrados, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This might suggest that temperature compensation has evolved in the natural range of the species favoring local adaptation. In accordance with this hypothesis, thermal adaptation along the latitudinal gradient of the species distribution has been evidenced in P. oceanica 78 , and the existence of local adaptation was recently suggested for C. nodosa , though in particular between Atlantic (Canary Archipelago) and Mediterranean populations 79 . In our analysis, this is further supported by the high number of genes differentially expressed on the basis of plants’ origin in P. oceanica with respect to C. nodosa (4,465 vs 1,009).…”
Section: Discussionmentioning
confidence: 52%